Analisis Respon Siswa terhadap Model Pembelajaran Contextual Teaching and Learning (CTL) pada Hasil Belajar Siswa Kelas VIII SMP Negeri Sukamana - Eva Juwita; Wahyu Arini (Journal on Education, 2025)
Analysis of student responses to the Contextual Teaching and Learning (CTL) learning model is expected to be able to see how much students respond to the CTL model. The analysis of the response is carried out to understand students' learning and learning challenges and use it as a guide for problem solving. This research aims to analyze the Contextual Teaching and Learning (CTL) method in science learning, especially science. The research method used is a qualitative approach by conducting teacher interviews and the teacher used in this research is a student response questionnaire for conducting interviews. The results of the research show that the conventional method used by teachers currently makes people feel bored because it only focuses on the teacher without any interaction between teachers and students who make students rarely understand the material as a whole which results in low student learning outcomes.The Contextual Teaching and Learning (CTL) approach can help students' involvement and understanding of the material. The results of student responses to the Contextual Teaching and Learning (CTL) learning model with an average percentage of 83.6 with 20 students responding and the total number of students obtained was 836 with a maximum score of 50. With student involvement in the learning process through the model In this CTL learning, students will better understand the material being taught so that it can improve student learning outcomes